Electrically Tunable Metasurface for Multi-Polarized Reflection - Bing Li; Yunhan Wang; Chunan Wang; Shiqi Liu (Remote Sensing, 2025)
Most electromagnetic metasurfaces only control a single property of electromagnetic waves, such as the phase, amplitude, polarization or frequency, leading to a shortage in capacity and security in communication and a decrease in radar imaging efficiency. By switching the states of four PIN diodes soldered between adjacent resonant arms, cross-polarization and co-polarization reflected waves both with a 1-bit phase can be implemented. The simulation results demonstrate that the proposed metasurface operates within a frequency band of 5.7 GHz to 5.88 GHz, covering ISM 5.8 GHz. Within its operational frequency range, in the cross-polarization reflection case, the losses of the 1-bit phase reflected wave are from 1 dB to 1.5 dB, with a high polarization conversion rate exceeding 91% and even reaching 99%. For the co-polarization reflection case, the losses of the 1-bit reflected wave are from 0.3 dB to 2 dB, and the polarization conversion is almost 100%. The phase difference of the reflected wave in both cases can be realized as about 180°, which satisfies the 1-bit phase requirement for building a good property of beam steering. Upon constructing a 10 × 10 small array, the cross-polarized reflection beam can be steered within the range of elevation angle from 0° to 45° and the elevation angle from 0° to 30° in the co-polarized reflection case.